Current state of digital transformation of russian banks - S. S. Matveevskii (Вестник университета, 2020)
The paper presents current state of digital transformation of Russian banks. The author defines the digitalization of banks as the introduction of FinTech technologies, close cooperation with Fintech-companies. Digitalization has both positive and negative consequences: cyber risks are growing, financial stability is decreasing. The analysis allowed the author to draw conclusions that the digital transformation of Russian banks is characterized by: the complex implementation of BCBS scenarios and the interaction between banks and Fintechcompanies, the emergence of neo-banks; increased competition in the banking sector; innovative opportunities for the production and sale of banking services and products, the emergence of new risks; accumulation and use of large amounts of data; the need to significantly change the information systems of banks (growth in demand for the services of IT companies); the emergence of ecosystems in which non-banking organizations are actively involved; large costs of Russian banks, which, as a rule, leads to an improvement in their financial results (as a result, medium and small banks begin to lose in the market).